Improved colored cubes teaching kit in representing and simplifying Boolean logic functions - Elewah, Ibrahim; Jalaleddine, Sara; Tbeileh, Omar A.; Yainnakou, Stavros; Kamzoul, Azzam; El-Morhabi, Sara; Tabet, Maria Gergi; Hafez, Rania (Institute of Advanced Engineering and Science, 2025)
This work presents, explains, and discusses a colored variables cubes teaching kit. The cubes teaching kit is designed based on the cubes method that was developed to graphically simplify the Boolean logic functions with three, four, five, and six variables. This renewed method is developed to overcome the limitation of the conventional Karnaugh maps method in terms of simplifying Boolean functions with a maximum of four variables only. Students can use the teaching kit to place each cube in its right position. Based on the label of each cube, students will be able to figure out the function minterm number. After that, the students will sort the cubes to represent the function. Eventually, the students will develop the competency to check the cubes adjacency, and this will lead them to formulate simplified Boolean expressions. Students' engagement is expected to improve when theoretical knowledge is implemented using a three-dimensional physical cube teaching kit. The aim of this work is that both the educators and students, in engineering and engineering technology programs, can benefit from the adaptation and even more from the modification of the proposed approach to facilitate the achievement of their learning objectives.